Examining Eco-psychological Connections in the Work of Han Kang: A Comparative Study of the novel The Vegetarian and We Do Not Part - Urwa Naeem; Dr. Hira Ali; Gulzar Bibi; Ayesha Bashir (Indus Journal of Social Sciences, 2025)
The present study seeks to explore the Eco- psychological interconnections in the context of two novels The Vegetarian and We do not Part written by Han Kang. Hence, the Primary focus of the study has been to examine the way human psychological state is interviewed with nature, ecological degradation and societal norms. Theodore Roszak (1992) concept of ecopsychology has been employed as the framework, while textual analysis method has been used for the purpose of data analysis. The findings revealed the emotional trauma and a sense of alienation that the both protagonists felt stemming from modern disconnections with the natural world. The findings also provide an insight ecological issue manifest with the human psyche especially in terms of gender, identity and cultural expectations.